Effectiveness of Iron Supplementation in Reducing the Incidence of Anemia in Adolescent Girls at Darussalam Wanaraja High School in Garut Regency in 2025 - Dina Mega Riana; Rita Ayu Ayu yolanda; Siti Hodijah (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Adolescents are a generation that needs to be prepared to contribute to national development and compete globally. Healthy, intelligent, and cheerful adolescents are the key to creating superior human resources (HR). Anemia remains a significant global health problem, particularly among adolescents and women of childbearing age. According to the World Health Organization (WHO, 2023), the prevalence of anemia among women aged 15–49 worldwide reaches 30.7%, while among pregnant women it reaches 35.5%, with the highest rates found in South Asia and Sub-Saharan Africa. This situation reflects that anemia remains a major challenge in efforts to improve the nutritional status and health of the global population. In Indonesia, a similar problem remains high (WHO, 2023). In West Java Province, the prevalence of anemia among adolescent girls remains relatively high and shows an increasing trend. Data from the West Java Provincial Health Office indicates that the prevalence of anemia among adolescent girls will reach approximately 45% in 2024, increasing to approximately 47% in 2025 (West Java Health Office, 2025). Darussalam Wanaraja High School, one of the schools within the Wanaraja Community Health Center (Puskesmas) working area, Wanaraja District, Garut Regency, also contributes to the highest incidence of anemia among adolescents compared to other schools in the same area. A common cause of anemia is a decrease in the number of erocytes or hemoglobin levels in the blood. Based on the above description, the researchers were interested in conducting a study entitled "The Effectiveness of Iron Supplementation in Reducing the Incidence of Anemia in Adolescent Girls at Darussalam Wanaraja High School, Garut Regency in 2026."